Kepatuhan Hukum Agen Laku Pandai BSI Smart dalam Pemberian Layanan Kepada Nasabah - Rahmawati, Heny; Shofiani, Trianah (el hisbah Journal of Islamic Economic Law, 2024)
Bank Syariah Indonesia (BSI) is one of the Islamic banks that organizes the Laku Pandai program under the name BSI Smart. This program is an extension of BSI in strengthening and expanding the inclusiveness and accessibility of the community to Islamic banking services and products. This study aims to analyze legal compliance and the impact of non-compliance with the law by BSI Smart agents at the Faculty of Islamic Economics and Business (FEBI), State Islamic University (UIN) Surakarta in providing services to customers. The type of research is juridical-empirical with a qualitative, conceptual, and legislative approach. Primary data was obtained through interviews with BSI Smart agents and customers, while secondary data came from regulations related to Laku Pandai, textbooks, research reports, and scientific journals. Data analysis techniques were carried out qualitatively through data reduction, data presentation, and drawing conclusions with a descriptive-analytical approach. The results of the study indicate that BSI Smart agents at FEBI UIN Surakarta have a low level of legal compliance. This is evidenced by the existence of a number of products that are subject to administrative fees that are not in accordance with the provisions set by BSI. The legal consequence of such non-compliance is the automatic closure of the BSI Smart application by the system. However, this action will be taken by BSI if there are reports or complaints from customers regarding the services provided by BSI Smart agents.